(untitled) (Stylos, 2019)
In this presentation we try to put the texts of two great representatives of classical culture in dialogue: Homer and Ovid. The three letters chosen from the Heroides (Penelope of Ulysses, Briseis to Achilles and Helena to Paris) work from the perspective of comparative literature taking into account, among others, the postulates of Graciela Reyes when she expresses: "there is no discourse that lacks any intertextual dimension: there is other text in all text" (P Textual 1984). Voices of the Greek texts are in the framework of the ovidian’s letters to tell the same myths, with a new way of saying. Ovid enjoys games with language as the word, which is Alpha and omega, allows you to offer a new vision of what sung by Homer.